A reflection on Human Rights in the Amazon and the anthropological Other: Looking at ourselves through the mirror - Fernandes, Estevão Rafael (International Journal for Innovation Education and Research, 2019)
How to realize universal rights in local realities? In order to answer this question, oneself make use of reflections on the anthropological "Other" as a way to deconstruct both speaking and ontological places, as well as the political and epistemological consequences of working human rights in different sociocultural contexts. One conclusion is that the very notion of humanism must be deconstructed. It reflects a system of values that is intended to be universal, taking local cultures as mere contingencies; as well as it takes its place as static, not as process, normalizing practices and domesticating specificities. It also shifts the deviants to the accepted matrix, imposing its own forms of construction of the subject; functions as a historical power device, relegating the alterities to "others," functioning as an instrument of social regulation; is based on the center / periphery dichotomy, reifying it.